2012
DOI: 10.1002/mrm.24115
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of MRI data encoded by multiple nonbijective curvilinear magnetic fields

Abstract: Parallel imaging technique using localized gradients (PatLoc) uses the combination of surface gradient coils generating non-bijective curvilinear magnetic fields for spatial encoding. PatLoc imaging using one pair of multipolar spatial encoding fields (SEMs) has two major caveats: 1) The direct inversion of the encoding matrix requires exact determination of multiple locations, which are ambiguously encoded by the SEMs. 2) Reconstructed images have a prominent loss of spatial resolution at the center of FOV us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 16 publications
0
44
0
Order By: Relevance
“…The former might be useful for Delta Relaxation Enhanced MR (dreMR) imaging (Alford et al 2009) and the latter for PATLOC (Hennig et al 2008; Schultz et al 2010; Lin et al 2012) or O-space style encoding (Stockmann et al 2010). …”
Section: Gradient Design and Implementationmentioning
confidence: 99%
“…The former might be useful for Delta Relaxation Enhanced MR (dreMR) imaging (Alford et al 2009) and the latter for PATLOC (Hennig et al 2008; Schultz et al 2010; Lin et al 2012) or O-space style encoding (Stockmann et al 2010). …”
Section: Gradient Design and Implementationmentioning
confidence: 99%
“…As an alternative to linear SEMs, nonlinear SEMs have been used to improve the dynamic range of MR signals (3) and to localize NMR signals without using selective excitation (4). Recently, it has been suggested that parallel imaging techniques using localized gradients (PatLoc) (5) can achieve a higher spatial resolution and reduce peripheral nerve stimulation using nonlinear surface SEM coils and an radiofrequency (RF) receiver array (6–8). O‐space imaging is a different imaging approach using the Z2 SEM together with linear SEMs to reconstruct accelerated images with high spatial resolution (9).…”
Section: Introductionmentioning
confidence: 99%
“…One price for using nonlinear imaging SEMs is that the images generally have anisotropic resolution and the image reconstruction becomes more complicated (8, 9). The anisotropic spatial resolution in PatLoc and O‐space imaging can be improved by using a combination of both linear and nonlinear SEMs in data acquisition (6, 7, 10). Also, PatLoc image reconstruction can be partially simplified using the iterative time‐domain reconstruction based on the conjugated gradient algorithm (7, 10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both SMASH/GRAPPA and SENSE, and indeed most of MRI, were designed to work with linear B 0 gradients. More recently, specialized non-linear gradient field coils [11] have been used with time varying gradient methods, like PatLoc [12][13][14], to reduce the ΔB max /Δt responsible for producing painful peripheral nerve stimulation. The efficiency of imaging with nonlinear B 0 encoding fields may be increased, for example in methods like O-space imaging [15] and null space imaging [16], by designing the B 1 fields to encode information complementary to that encoded by the SEM.…”
Section: Introductionmentioning
confidence: 99%